Enhancement-mode AlGaN/GaN HFET with buried-junction-barrier for breakdown improvement and threshold-voltage modulation. (October 2018) - Zhou, Qi; Wei, Dong; Zhu, Ruopu; Dong, Changxu; Huang, Peng; Zhang, Anbang; Shi, Yuanyuan; Zhu, Liyang; Shi, Yu; Cheng, Qian; Deng, Cao; Chen, Wanjun; et al.
Abstract: A novel AlGaN/GaN heterojunction field-effect transistor (HFET) with buried-junction-barrier (BJB) is proposed in this work. In the BJB-HFET, a thin PGaN layer was inserted in the unintentionally doped GaN channel layer, which introduces a buried PN-junction beneath the gate region. Owing to the presence of the PN-junction, in "OFF-state", a reverse-biased barrier for electrons is formed along the channel in GaN buffer, which effectively reduces the buffer leakage current of the device. Moreover, the BJB also facilitates to obtain a uniform electric-field (E-field) distribution in the depletion region that dictates breakdown voltage ( BV ) improvement. For a AlGaN/GaN BJB-HFET with a gate-drain distance of 5 μm, a BV as high as 1190 V at leakage current of 10 μA/mm is achieved with a low specific on-resistance ( R on, sp ) of 0.54 mΩ cm 2, which yields a significantly high Baliga's Figure-of-Merit ( FOM ) of 2.83 GW/cm 2 . Besides, benefiting from the energy-band modulation capability of the BJB structure, a higher threshold-voltage ( V th ) can be simultaneously obtained in the BJB-HFET compared with the conventional heterojunction field-effect transistor (Conv. HFET). The proposed BJB structure is of great potential for high performance AlGaN/GaN power transistors. Highlights: A novel high breakdown voltage AlGaN/GaN HFET features a locally buried PGaN layer in the GaN channel layer. The BV of the device is improved from 383 to 1190 V at leakage current as low as 10 μA/mm by using the PGaN acting as a buried-junction-barrier. Meanwhile, as the BJB structure locates beneath the gate region in GaN buffer, the device also features high threshold-voltage and low specific ON-resistance leading to a good trade-off between the on-state and off-state performance.